Epitaxial co-deposition growth of CaGe2 films by molecular beam epitaxy for large area germanane. Issue 3 (27th January 2014) - Pinchuk, Igor V.; Odenthal, Patrick M.; Ahmed, Adam S.; Amamou, Walid; Goldberger, Joshua E.; Kawakami, Roland K.
Abstract